Phylogenetic group-based assembly and co-occurrence pattern of the microbial community in full-scale wastewater treatment plants during the Chinese spring festival. (March 2023) - Cui, Hongcan; Xu, Ronghua; Yu, Zhong; Meng, Fangang
Abstract: The quality and quantity of domestic sewage discharge vary significantly during the Chinese Spring Festival due to the huge population shift. The dynamics of microbial community traits during the Spring Festival, particularly the phylogenetic group-based assembly and co-occurrence patterns, are however little understood. Here, influent and activated sludge samples from 2 full-scale wastewater treatment plants were collected bi-daily throughout a 20-day Spring Festival period and subjected to high-throughput Illumina-MiSeq sequencing. The findings revealed that the microbial communities in the activated sludge displayed a comparatively stable pattern, and that the influent communities experienced significant temporal fluctuations in terms of diversity and composition. The characterization by "Infer Community Assembly Mechanisms by Phylogenetic-bin based null model" demonstrated that for Competibacter glycogen-accumulating organisms, the assembly mechanism shifted from deterministic process (HoS = 69.5%) before the Spring Festival to stochastic process (DR = 65.9%) after the Spring Festival. The network analysis revealed that the network structure of sludge communities was more stable before the Spring Festival than that after the Spring Festival. Additionally, sludge communities had no keystone species in common with the influent before the Spring Festival, while the sludge and influent communities shared two keystone taxa after the Spring Festival (Sebaldella and Candidatus Competibacter). This study would deepen our understanding of the microbial ecology in biological wastewater treatment systems, which also aids in managing wastewater treatment plants. Graphical abstract: Image 1 Highlights: Microbial community in influent fluctuated substantially during spring festival. Functional bacteria like GAO and PAO increased obviously after spring festival. The network structure of the AS community was more stable than that of influent. Sludge network shared more keystone taxa after the Spring Festival. Assembly mechanism of GAO changed to stochastic process after the Spring Festival.